Dielectric Properties of BaZr0.2[Ti(1-x)Mgx/3Ta2x/3]0.8O3 Solid Solution - Kavil, Jithesh; Varghese, Jobin; Kovummal, Govind Raj (Frontiers in Materials, 2021)
BaZr0.2[Ti(1-x)Mgx/3Ta2x/3]0.8O3 (x = 0.0, 0.05, 0.1, 0.2, 0.4, 0.6, 0.8, 1.0) (BZTMT) ceramics were prepared through conventional solid state ceramic route. The crystal structure and microstructure of the compounds were investigated respectively using XRD and SEM. The dielectric properties were measured in the frequency range of 100 Hz–1 MHz. The ferroelectric Curie temperature of BaZr0.2Ti0.8O3 (x = 0) shifted from 21°C to -10°C with the addition of minute amount of dopant (x = 0.025) and the paraelectric transition temperature is diffusive in nature. The relative permittivity and dielectric loss of BZTMT at 1 MHz varies from 5205 to 24 and 1.8 × 10–2 to 2.0 × 10–5 respectively, as the value of x increases from 0 to 1.